2003
DOI: 10.1023/a:1024299523852
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Our data show that the studied alterations in cholesterol values, coagulation parameters, increased mean blood pressure values and myocardial necrosis markers are strictly related to modified plasma nitric oxide levels, and that the regulation of nitric oxide metabolism affects the presence or absence of some coronary disease risk factors (lipid, coagulation and blood pressure alterations) and plasma indicators of myocardial necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
2
3
0
1
Order By: Relevance
“…Results from the present study corroborate the importance of the bio-availability of NO in lipid metabolism as administration of L-NAME (which is a well-known non-selective inhibitor of nitric oxide synthase) in the present study in rats led to hypercholesterolemia and hypertriglyceridemia (Table 5). This is in agreement with earlier studies done by Pinelli et al (2003) and Goudarz et al (2009) in rabbits treated with L-NAME. Pinelli et al demonstrated that reduced NO availability increased the incorporation of labeled precursors in the cholesterol pathway and decreased cholesterol catabolism as a result of the inhibition of 7α-hydroxylase activity (Pinelli et al, 2003).…”
Section: Re Sults 4 | Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Results from the present study corroborate the importance of the bio-availability of NO in lipid metabolism as administration of L-NAME (which is a well-known non-selective inhibitor of nitric oxide synthase) in the present study in rats led to hypercholesterolemia and hypertriglyceridemia (Table 5). This is in agreement with earlier studies done by Pinelli et al (2003) and Goudarz et al (2009) in rabbits treated with L-NAME. Pinelli et al demonstrated that reduced NO availability increased the incorporation of labeled precursors in the cholesterol pathway and decreased cholesterol catabolism as a result of the inhibition of 7α-hydroxylase activity (Pinelli et al, 2003).…”
Section: Re Sults 4 | Discussionsupporting
confidence: 94%
“…This is in agreement with earlier studies done by Pinelli et al (2003) and Goudarz et al (2009) in rabbits treated with L-NAME. Pinelli et al demonstrated that reduced NO availability increased the incorporation of labeled precursors in the cholesterol pathway and decreased cholesterol catabolism as a result of the inhibition of 7α-hydroxylase activity (Pinelli et al, 2003).…”
Section: Re Sults 4 | Discussionsupporting
confidence: 94%
“…MI experimental models have been widely used in research to evaluate the pathophysiology and protective effect of natural products on different species. Although there are several MI experimental models, isoproterenol-induced MI presents a greater similarity to human MI, since it meets the requirements of the Fourth Universal Definition of Myocardial Infarction (2018) that includes increased myocardial injury, histological alterations, reduction of antioxidant enzyme activity, inflammatory process, myofibrillar degeneration, and necrosis. …”
mentioning
confidence: 99%
“…In addition, Tet has antihepatic fibrosis (Teng et al, 2015;Zhang, 2016) and cardiomyocyte fibrosis (Gan et al, 2018) and has been used to treat silicosis with fibrosis. In addition, Tet (Yu et al, 2001;Meng et al, 2008;Pinelli et al, 2010;Xu et al, 2010;Huang et al, 2011;Zhang et al, 2017a; protects the cardiovascular system through mechanisms such as antihypertensive, antiarrhythmic and anti-myocardial ischemia and reperfusion injury. Also, Tet has antibacterial (Lee et al, 2012; and activates mesenchymal stem cells to enhance immunomodulation .…”
Section: Clinical Application Of Tetrandrinementioning
confidence: 99%
“…Tet has a variety of pharmacological activities, including anti-tumor, anti-inflammatory, anti-cellular fibrosis, cardiovascular protection as well as antioxidant, antiviral, and immune enhancement. It protects the cardiovascular system through hypotension, antiarrhythmia, and anti-myocardial ischemia and reperfusion injury (Yu et al, 2001;Pinelli et al, 2010;Xu et al, 2010;Huang et al, 2011;Zhang et al, 2017a;, in addition to its antibacterial (Lee et al, 2012;Li et al, 2021) and activation of mesenchymal stem cells to enhance immune regulation .…”
Section: Introductionmentioning
confidence: 99%